The Influence of Mental Imagery on Mastering Basic Forehand Groundstroke Skills in Tennis - Agustryani, Resty; Soraya, Novi (Indonesian Journal of Sport Management, 2025)
Background: One of the sports that requires a good combination of technique, physical and mental abilities is tennis. One of the basic techniques that must be mastered is Forehand Groundstroke. Purpose: To see the effect of mental imagery on Basic Tennis Forehand Groundstroke Skills. Methods: This research uses a quantitative approach, with a quasi-experimental design and pretest-posttest control group design techniques. This technique compares an experimental group that uses mental imagery and a control group that does not use mental imagery. The implementation of the research started from a pretest which was carried out before the treatment was applied. Then 4 weeks of training were carried out with the experimental group using mental imagery and the control group only doing conventional forehand groundstroke training without additional mental imagery. The data obtained was analyzed using the t-test statistical test to see whether there were significant differences between the experimental group and the control group before and after treatment. Analysis is carried out with the help of statistical software such as SPSS. Results: Basic Forehand Groundstroke Tennis Skills The group that received the mental imagery method was better than the control class. Conclusion: Based on the results of research that has carried out data processing and analysis, it can be concluded that Mental Imagery influences Mastery of Basic Forehand Groundstroke Skills in Field Tennis. This can be seen from the results of hit accuracy (towards a certain target); Hit strength (ball speed after being hit); The consistency of strokes (the number of strokes that managed to enter the opponent's playing area) was significantly different when compared to the group that did not use the mental imagery method. Implications and Recommendation: From the results of this research, mental imagery can be used as an alternative to train students taking tennis courses.